Ugoy ng duyan - Puzon, Maria Isadora C. 1979-; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
"Ugoy ng Duyan" is a 12-minute narrative film showing the deep relationship developed by a father and daughter during the time that she was raised by her father alone. But that relationship leads to the girl's estrangement to her own mother. It was made during the first semester of the academic year 2000-2001. The filmmaker chose to make a film about this topic because of her own deeply personal conflicts raised by a situation similar to that of her main character. This paper acts as documentation for the said film from the time the film was conceptualized to its completion. Herein also is explanation for why one would choose to make a film that resurrects old wounds and conflicts.
Vita.
Thesis (A.B. Film and Audiovisual Communication)--University of the Philippines Diliman
Keywords: Ugoy ng duyan (Short films -- Philippines).; Mother and child -- Philippines; Father and child -- Philippines